International differences in well-being - Diener, Ed.; Helliwell, John F.; Kahneman, Daniel, 1934- (Oxford : Oxford University Press, 2010)
Starting from many different vantage points, the book reaches a consensus that many measures of subjective well-being, ranging from life evaluations through emotional states, based on memories and current evaluations, merit broader collection and analysis.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Well-being -- Cross-cultural studies; Quality of life -- Cross-cultural studies; Social indicators -- Cross-cultural studies